2022
DOI: 10.3390/cells11182834
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Comparison of Synthetic Macroporous Filamentous and Sponge-like Skin Substitute Matrices Reveals Morphometric Features of the Foreign Body Reaction According to 3D Biomaterial Designs

Abstract: Synthetic macroporous biomaterials are widely used in the field of skin tissue engineering to mimic membrane functions of the native dermis. Biomaterial designs can be subclassified with respect to their shape in fibrous designs, namely fibers, meshes or fleeces, respectively, and porous designs, such as sponges and foams. However, synthetic matrices often have limitations regarding unfavorable foreign body responses (FBRs). Severe FBRs can result in unfavorable disintegration and rejection of an implant, wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…Electrospun fibres are known for resembling the nanofibrous ECM structure and are therefore widely used in the tissue engineering field [26]. If compared to polymer films, electrospun fibres also seem to induce the formation of thinner fibrous capsules, reducing scaffold isolation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Electrospun fibres are known for resembling the nanofibrous ECM structure and are therefore widely used in the tissue engineering field [26]. If compared to polymer films, electrospun fibres also seem to induce the formation of thinner fibrous capsules, reducing scaffold isolation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Barsch et al examined whether inflammation and FBR were significantly influenced by the 3D biomaterial design by comparing filamentous fleece and sponge-like biomaterial in a porcine model. Although no statistically significant difference could be found regarding FBR, the sponge-like synthetics showed a significantly lower inflammatory reaction which was quantified based on the density of polymorph-nucleated cells [210]. A further component of biocompatibility is the degradation of biomaterials and the tissue reaction to the degradation products.…”
Section: Importance Of Nanomaterials Characteristicsmentioning
confidence: 92%
“…However, multiple big pores might negatively affect the mechanical stability of the structure, so an adequate balance needs to be found. In addition to crucial scaffold properties, several studies demonstrated that fibrotic capsule was formed around scaffolds with smooth surface [ 216 ].…”
Section: Interaction Between Biodegradable Scaffolds and Host Immune ...mentioning
confidence: 99%